PEMBERDAYAAN DAN BIMBINGAN TEKNIS KADES POSYANDU DALAM MENGHADAPI BENCANA BANJIR - M. Alif; V.P. Damayanti (Buletin Udayana Mengabdi, 2024)
The flood disaster in 2021 in South Kalimantan Province resulted in 35 people dying, 876 injured, 190,191 displaced, 101,706 houses affected by flooding, 633,723 residents affected, and 20,791 displaced and resulted in damage to houses, public and social infrastructure, and facilities with a severe level, medium or light. damage, consequences, and impacts of floods and landslides. The purpose of this community service is for Posyandu cadres to play an active role in disaster management. This community service activity is carried out to increase the knowledge, attitudes, and skills of Posyandu cadres when a disaster occurs, especially a flood disaster. The method used is to conduct counseling, outreach, demonstrations, and simulations. The activities carried out are providing socialization on the role of posyandu cadres during a disaster, techniques for carrying babies during disasters so that babies are calm and providing training in making complementary food during disasters. Posyandu cadres and participants can understand and know the role of cadres during a disaster and after a disaster and can practice all the technical guidance that has been implemented. Keywords: Empowerment, Posyandu, Disaster, Flood